A randomized clinical trial investigating treatment choice in Chinese men receiving sildenafil citrate and tadalafil for treating erectile dysfunction - Bai, Wen-Jun; Li, Hong-Jun; Jin, Jian-Jun; Xu, Wen-Ping; Sebastian, Sorsaburu; Wang, Xiao-Feng (Asian journal of andrology, 2017)
Sildenafil and tadalafil are efficacious and well tolerated in Chinese men with erectile dysfunction （ED）. Recent study results indicate that men with ED in China who were naive to phosphodiesterase inhibitor type 5 （PDE5） therapy prefer tadalafil 20-mg （on-demand） versus sildenafil 100-mg （on-demand）. Differences in psychosocial outcomes may help to explain treatment preference in favor of tadalafih This open-label, randomized, crossover study compared psychosocial outcomes and drug attribute choices between tadalafil and sildenafil in Chinese men with ED na＇（ve to PDE5 inhibitor therapy. Eligible patients were randomized to sequential 20-mg tadalafU/lOO-mg sildenafil （n = 190） or 100-mg sildenafil/20-mg tadalafil （n = 193） for 8 weeks each and were asked which treatment they preferred to take for the 8-week extension phase. Psychosocial outcomes were assessed using the Psychological and Interpersonal Relationship Scale （PAIRS）, Drug Attributes Questionnaire （DRAQ）, and Sexual Life Quality Questionnaire （SLQQ）. When taking tadalafil versus sildenafil, men had a higher mean endpoint score on the PAIRS Spontaneity Domain （tadalafil = 2.86 vs sildenafil = 2.72; P 〈 0.001）, and a lower mean endpoint score on the Time Concerns Domain （tadalafil = 2.41 vs sildenafil = 2.55; P 〈 0.001）. A numerical increase in the Sexual Self-Confidence Domain was observed when taking tadalafil versus sildenafil （tadalafil -- 2.76 vs sildenafil = 2.72; P= 0.102）. The most frequently chosen drug attributes explaining treatment preference were able to get an erection long after having drug, and ability to get an erection every time. SLQQ results were comparable between treatment groups. These psychosocial outcomes may explain why more Chinese men preferred tadalafil versus sildenafil for the treatment of ED in this clinical trial.